Ayurvedic Management of Endometriosis (International Journal of Ayurveda and Pharma Research, 2025)
Endometriosis is a painful and chronic condition that affects women of reproductive age, marked by the growth of endometrial-like tissue outside the uterine cavity. It is accompanied by debilitating pelvic pain, infertility, and potentially malignant transformations, significantly impacting quality of life. Endometriosis affects an estimated 1 in 10 women of reproductive age worldwide. The ovaries and pelvic peritoneum are the most common sites for developing endometriotic lesions. This is the case report of a 24year old unmarried female, who presented with irregular menstrual cycles with heavy menstrual bleeding and severe dysmenorrhea associated with giddiness, vomiting. On USG she was diagnosed with right ovarian endometriotic cyst. Based on the clinical features presented by the patient, medications possessing Amapachana, Agnideepana, Kaphapittasamana, Vataanulomana, Granthihara and Lekhana properties were administered. After seven months of internal medications symptoms reduced considerably and there was no ovarian endometriotic cysts in USG.